Structure of the substrate‐binding domain of Plasmodium falciparum heat‐shock protein 70‐x. Issue 10 (2nd October 2020) - Schmidt, Julia; Vakonakis, Ioannis
Abstract : The 3.25 Å resolution crystallographic structure of the substrate‐binding domain of the erythrocyte‐exported Hsp70 chaperone from the malaria parasite Plasmodium falciparum was determined. The parasite domain is shown to be highly similar to the equivalent domain of a human Hsp70 chaperone in structure and mode of substrate engagement. Abstract : The malaria parasite Plasmodium falciparum extensively modifies erythrocytes that it invades by exporting a large complement of proteins to the host cell. Among these exported components is a single heat‐shock 70 kDa class protein, PfHsp70‐x, that supports the virulence and growth rate of the parasite during febrile episodes. The ATP‐binding domain of PfHsp70‐x has previously been resolved and showed the presence of potentially druggable epitopes that differ from those on human Hsp70 chaperones. Here, the crystallographic structure of the substrate‐binding domain (SBD) of PfHsp70‐x is presented in complex with a hydrophobic peptide. The PfHsp70‐x SBD is shown to be highly similar to the counterpart from a human erythrocytic Hsp70 chaperone. The binding of substrate at the interface between β‐sandwich and α‐helical subdomains of this chaperone segment is also conserved between the malaria parasite and humans. It is hypothesized that the parasite may partly exploit human chaperones for intra‐erythrocytic trafficking and maintenance of its exported proteome.